2008
DOI: 10.1142/s0217732308028430
|View full text |Cite
|
Sign up to set email alerts
|

Channeling Effect and Improvement of the Efficiency of Charged Particle Registration With Crystal Scintillators

Abstract: Energy of ions (recoil nuclei) channeled along definite directions in crystals is transferred to the lattice electrons mainly. In NaI(Tl)-type scintillators, this leads to increasing the light yield from ∼10% to ∼100% when compared with the yield for electrons of the same energy. Taking into account this effect at processing data of DAMA/NaI experiments in Gran Sasso, which had demonstrated the year modulation of number of signals in a range of 2-6 keV of electron equivalent, reveals that DAMA/NaI results coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…In Refs. [38,39] it has been pointed out that the socalled channeling effect could be relevant, implying that for a certain fraction of events no quenching would occur due to the special orientation of the recoil with respect to the crystal. So far this effect has not been confirmed experimentally in the relevant energy range.…”
Section: Event Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [38,39] it has been pointed out that the socalled channeling effect could be relevant, implying that for a certain fraction of events no quenching would occur due to the special orientation of the recoil with respect to the crystal. So far this effect has not been confirmed experimentally in the relevant energy range.…”
Section: Event Ratesmentioning
confidence: 99%
“…Details on how we calculate the matrix elements involving the wave function in Eq. (38) are given in Appendix C.…”
Section: B Wimp-atom Scatteringmentioning
confidence: 99%
“…by Drobyshevski [1] and subsequently by the DAMA collaboration [2] in 2007. In 2008, Avignone, Creswick, and Nussinov [3] suggested that a daily modulation due to channeling could occur in NaI crystals, which would be a background free dark matter signature.…”
mentioning
confidence: 99%
“…[48] Most (∼ 97%) of DAMA's data are in the 3 − 6 keV range. If we identify these as the unchanneled sample then the true energies are ∼ 30−60 keV and channeling effects are much smaller.…”
Section: Dama/libra the Annual Modulations And Prospects Of Daimentioning
confidence: 99%